Systematic engineering of Pichia pastoris for high-level production of recombinant human granulocyte-macrophage colony-stimulating factor - Zhenzhen Cheng; Keyu Gong; Yuchao Song; Zhenchang Guo; Wenjun Guan (Bioresource Technology, 2026)

DDX39B drives the m6A modification of LDHA to promote trophoblast proliferation - Cheng Li; Wenjun Zhou; Yuqin Shen; Jing Zhang; Yanqiong Jiang; Ruiman Li (Molecular Genetics and Genomics, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Tracking sedimentation process under progressive mangrove propagation in low-energy bays - Weiming Li; Zhijun Dai; Xuefei Mei; Jiejun Luo; Wenjun Zeng; Ping Zhang; Ran Chen; Jinping Cheng (Marine Geology, 2026)

UV-based homogeneous disinfection process for removal of antibiotic resistance genes: Efficiency, mechanisms and influencing factors - Wenkui Xu; Xiangqin Zhou; Qihong Liu; Chen Yan; Jing Liu; Xinyue Yang; Wenjun Wang; Biao Song; Min Cheng; Chengyun Zhou; Wenjun Yin (Journal of Environmental Sciences, 2026)

Structure-dependent effects of flavan-3-ols on 3-aminopropionamide deamination and acrylamide formation in the Maillard reaction - Yajing Qi; Wenjun Wang; Jiahao Cheng; Bin Xu (Food Research International, 2026)

Unraveling the tunnel dynamics of enzymes: a rational design strategy for robust biocatalysis in organic solvents - Wenjun Cheng; Yuan Qi; Binbin Nian; Xing Sun (Food Chemistry, 2026)

Carbon dot-based gel-state emissive layer for light-emitting-diode with pure white emission - Dongren Zheng; Tianyang Zhang; Haizhou Yu; Xiangyong Meng; Wenjun Yang; Hui Huang; Cheng Zhu; Yang Liu; Zhenhui Kang (Chemical Engineering Journal, 2026)

Establishment of a disease model for Mycoplasma Ovipneumoniae infection in Hu sheep and its lung transcriptomic analysis - Guangxin Zhao; Guojie Cheng; Wenjun Liu; Kepeng Guo; Yanming Sun; Yanbing Zhang (Veterinary Immunology and Immunopathology, 2026)

The independent and joint effects of short-term exposure to ambient air pollutants on eczema in two cities of China - Tianjing Ouyang; Zhuoxuan Liang; Shujie Huang; Yingyin Liu; Ziqiang Lin; Qijiong Zhu; Weiquan Zeng; Yu Wang; Changchang Li; Jianxiong Hu; Guanhao He; Tao Liu; et al. (Journal of Hazardous Materials, 2026)

Modulating electronic structure via N-doping and built-in electric field in CoO@Co9S8 heterostructure for enabling bidirectional sulfur redox in high-performance LiS batteries - Henan Jia; Wenjun Zhang; Jiayi Luo; Mingwei Liu; Taotao Guo; Fuling Tang; Mao-Cheng Liu; Yaotian Yan; Junlei Qi (Chemical Engineering Journal, 2026)

High-level estrogen impairs memory via estrogen receptor signaling in a hypothalamic–hippocampal neural circuit - Xin Li; Nan Zang; Qianru Zhao; Yuxiang Sun; Udhaya Kumar Siva Kumar; Mengyu Hua; Wenjun Zhou; Yanyan Qi; Hu Chen; Longqing Xia; Jun Qin; Lei Sun; et al. (Science Bulletin, 2026)

Using network pharmacology and structural biology to elucidate the molecular mechanism by which Macrolactin A protects against aphids - Min Cheng; Aoping Tan; Ruyi Ma; Shibo Yang; Ziang Zhou; Kangbo Zhao; Mengqian Guo; Ting Guo; Wenjun Wu; Hong Xu; Shaopeng Wei; Nana Wang; et al. (Pesticide Biochemistry and Physiology, 2026)

Promoting the excitation of ferrate(VI) with copper oxide nanoparticles for the degradation of 2,4-dichlorophenol - Guihai Zhang; Yidan Luo; Wenjun Zeng; Yingshuai Zhang; Jiancheng Cheng; Xinlong Hua; Mengqin Yu; Yalan Zhang; Wei Liu; Xianchuan Xie; Zugen Liu (Journal of Water Process Engineering, 2026)

Origins of Miocene basaltic magmatism in the western Yarlung-Tsangpo Suture Zone, southern Tibet: Insight into the lateral and longitudinal tearing of the subducted Indian continental slab - Jianbo Cheng; Xianshu Dong; Yalin Li; Shuai Li; Siqi Xiao; Wenjun Bi; Rui Zhou (Chemical Geology, 2026)

Highly sensitive m6A electrochemical biosensor based on laser-induced graphene electrodes functionalized with DNA tetrahedron/gold-antibody nanoparticle - Huiyan Cao; Xi Cheng; Li Huang; Haotian Zhang; Ziyi Liu; Wenjun Yang; Song-Mei Liu; Fang Wang (Analytica Chimica Acta, 2026)

Numerical Study of Multi-cluster Hydraulic Fracture Propagation in Deviated Horizontal Wells - Wenjun Xu; Zhenwei Bai; Leiming Cheng; Lei Wang; Junjie Liu; Chen Hao; Sheik S. Rahman (Rock Mechanics and Rock Engineering, 2026)

Construction and validation of a fast selective catalytic reduction (SCR) strategy for enhancing low-temperature activity of zeolite catalysts under microwave irradiation - Xiangru Li; Yun Chen; Xuehong Zi; Jinyu Yuan; Yao Cheng; Xiaoqian Cheng; Kaiyu Hu; Boxuan Song; Wenjun Liang; Liyun Song (Journal of Environmental Chemical Engineering, 2026)

Change of global precipitation during strong El Niño under high-emission scenarios - Wenjun Sang; Yu Huang; Zhigang Cheng; Yaohui Li; Lian Duan; Wenwen Xu; Ruping Zhang (Frontiers of Earth Science, 2026)

Non-radical PMS activation for simultaneous nitrite and sulfamethoxazole removal with inhibited nitrobyproduct formation - Jiawei Lin; Wenjun Zhou; Jiaqi Peng; Yongyou Hu; Hongfeng Zhang; Cheng Zhao; Qi Shan; Hao Zhou; Yi Yin (Journal of Water Process Engineering, 2026)

Progress in Degradation of Volatile Organic Compounds by Biochar Fillers - Miaomiao Qu; Renlei Zhou; Zhuowei Cheng; Qiwen Luo; Yuqi Feng; Yun Shi; Wenjun Wang; Jianmeng Chen; Minmin Zhang (Water, Air, & Soil Pollution, 2026)

C-type porous starch microgels for robust lutein Mickering emulsions - Can Zhao; Yu Cheng; Wenjun Li; Li Yuan; Xingbin Yang; Zhong Zhang (Journal of Food Engineering, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Proanthocyanidins in food and health: structure–activity relationships, application challenges, and emerging strategies - Ziyu Li; Wenjun Wang; Ping Cheng; Qirong Dong; Haiqi Chen; Kai Fu; Chao Fu; Yunfeng Pu; Donghong Liu (Food Chemistry, 2026)

Association between temperature and respiratory hospitalizations: Do temperature data sources and exposure measurements matter for impact assessment? - Desheng Zhao; Wenjun Cheng; Zien Jin; Yongmei Su; Liwei Zhang; Yanan Ouyang; Yujia Zhai; Yiyun Ding; Chun Zhao; Xuejing Cao; Jian Cheng (Environmental Research, 2026)

MoS2/rGO/MXene/TiO2 composite aerogel with enhanced Mott-Schottky effect for achieving multifunctionality and broadband microwave absorption - Naixin Zhai; Zihao Wang; Zhenzhi Cheng; Lelin Xu; Wenjun Yang; Weiping Zhou; Fei Gao; Xiaojun Zeng; Guangsheng Luo (Chemical Engineering Journal, 2026)

APMAP regulated by YY1 transcription mediates ferroptosis and metastasis in non-small cell lung cancer through the PI3K/AKT/mTOR pathway - Xiaohong Zhuang; Shu Lin; Cheng-sheng zhang; Qi Qin; Qixing Yan; Jing-ru Luo; Wenjun Tang (Journal of Molecular Histology, 2026)

Flavor improvement in enzymatically hydrolyzed Citrus Huyou peel residues: based on sensory and multi-omics analysis - Jiabao Huang; Xinyue Zhou; Han Wang; Qiong Huang; Jinting Li; Cheng Zeng; Wenjun Wang; Donghong Liu (Food Chemistry, 2026)

The double driving mechanism involved ultrafast Fenton-like process for efficient degradation of pharmaceuticals in hospital wastewater - Yin Zhou; Fanzhi Qin; Wenjun Wang; Cheng Huang; Changlan Hou; Jian Hu; Deyu Qin; Hao Weng; Hanzhuo Luo; Qun Fang; Yunbo Zhai; Chen Zhang (Chemical Engineering Journal, 2026)

Sunlight and suicide risk: mediating effect of high temperature in China - Xiuya Xing; Yiming Gai; Qin He; Wenjun Cheng; Jingli Zhu; Qianyao Cheng; Yinguang Fan; Hong Su; Huadong Wang; Zhongliang Bai; Jian Cheng (International Journal of Biometeorology, 2026)

Intermodulation of endoplasmic reticulum stress and ferroptosis in diabetic nephropathy: molecular mechanisms and therapeutic potentials - Jiyang Wang; Fengxia He; Runxiu Wang; Fangqin Zou; Wenjun Yan; Shengyu Cheng; Rui Liu; Xianghong Lei (Apoptosis, 2025)

Damage investigation of segmental lining in underwater pipeline tunnels based on plastic hinge theory - Xudong Cheng; Yanzhao Li; Wenjun Hu; Xingji Zhu (European Journal of Environmental and Civil Engineering, 2025)

Miocene N-MORB- and OIB-type diabase dikes in the western Yarlung Tsangpo suture zone, southern Tibet: Insights into the Indian slab tearing and asthenosphere–lithosphere interaction - Jianbo Cheng; Yalin Li; Xianshu Dong; Siqi Xiao; Shuai Li; Wenjun Bi; Rui Zhou (Lithos, 2025)

Potential applications of lipases rational design in the synthesis of medium- and long-chain triglycerides: Current advances and perspectives - Yiran Han; Hao Fang; Xiaoyu Nie; Xuanling Zhang; Zeping Lu; Binbin Nian; Yi Hu; Wenjun Cheng (Food Chemistry, 2025)

Critical hydro-geomorphological characteristics related to lateral erosion–deposition difference within the multilevel bifurcation system of the Yangtze Estuary, China - Boyuan Zhu; Shiyu Zhang; Lingling Zhu; Lingfeng Liu; Wenjun Yu; Jinwu Tang; Yongzhou Cheng; Yitian Li; Alistair G.L. Borthwick (Journal of Hydrology, 2025)

Excellent energy storage density of Bi-doped CaTiO3 linear dielectrics - Kun Chen; Wenjun Cao; Yanwei Wu; Chao Cheng; Yingtang Zhang; Jun Zheng; Shouguo Huang; Yi Yu; Chunchang Wang (Chemical Engineering Journal, 2025)

Spatial–Temporal Dynamics of Drought Characteristics and Its Influencing Factors on Tibetan Plateau - Zhizhu Zhou; Wenjun Yu; Lin Zhao; Yanzhong Li; Shuo Cheng; Jiazhe Duan; Yincong Xing; Wei Shao (International Journal of Climatology, 2025)
Assessing drought on the Tibetan Plateau (TP) is essential for understanding the spatial characteristics of the region's hydrological regimes, as well as the trends of the evolving climate‐ecological system. Based on the precipitation and the potential evapotranspiration data from the ERA5‐Land dataset, this study evaluated the drought characteristics on the TP from 1950 to 2022 using the Standardised Precipitation Evapotranspiration Index (SPEI) and the Run theory. The analysis of SPEI at multiple time scales—SPEI‐1 (monthly), SPEI‐3 (seasonal), and SPEI‐12 (annual)—consistently revealed a pronounced drying trend across the TP over the past 70 years. Notably, the wet‐to‐dry transition points were detected in 2000 and 2001 based on the SPEI‐1 and SPEI‐3 series, respectively, while the SPEI‐12 series indicated a later shift occurring in 2004. In addition, the SPEI values indicated a spatial trend of increasingly severe drought conditions from south to north. Particularly, pronounced drought stress was observed in the Brahmaputra, Ganges, and Indus basins, as well as in the southern regions of the Inner Plateau. Furthermore, the relationships between drought variability and key climatic drivers—including sunspots, El Niño‐Southern Oscillation (ENSO), temperature (TEMP), and annual mean areal precipitation (AP)—were identified through cross‐wavelet transform (XWT) and wavelet coherence analysis (WTC). In general, the analysis showed that the SPEI values on the TP were negatively correlated to ENSO and TEMP but positively correlated to sunspots and AP. This study offers a comprehensive spatiotemporal assessment of drought dynamics across the TP, providing critical insights for regional water resource management and climate change adaptation planning.

RNA target-independent non-canonical activation (RINCA) of Cas13 trans-nuclease activity - Wenjun Liu; Xuena Zhu; Yuanyuan Xue; Xiaoyan Wang; Lei Chang; Shanshan Wang; Ling Li; Jinyan Huang; Ying Zhang; Cheng Jiang; Hongjie Chi; Yanbin Zhang; et al. (Science Bulletin, 2025)

Integration of moving bed biofilm reactor and gravity-driven membrane bioreactor for decentralized domestic wastewater treatment: Efficiency and mechanistic insights - Zixin Ma; Ziao Zhang; Shilei Fu; Linqiao Jiang; Yitong Sun; Yichun Zhu; Yanrui Wang; Wenjun Cheng; Xiaobin Ma; Heng Liang; Xiaobin Tang (Bioresource Technology, 2025)

Plant hormones mediated temperature-induced anthocyanin accumulation in blood oranges (Citrus sinensis L. Osbeck) - Jin Chen; Jianle Chen; Yujing Sun; Wenjun Wang; Yanyun Zhu; Shiguo Chen; Xingqian Ye; Donghong Liu; Zhongxiang Fang; Huan Cheng (Food Bioscience, 2025)

Sedimentary geochemical records of the palaeovegetation and palaeoclimate evolution in the Pinghu Formation, Western Slope Belt, Xihu Sag, East China Sea Basin - Yanan Wang; Lin Wei; Xiong Cheng; Hui Diao; Wenjun Li; Dujie Hou; Jiansheng Li (Organic Geochemistry, 2025)

Protection of lipase by self-assembled microgels under high-pressure - Yu Cheng; Lulu Liu; Can Zhao; Xiaolin Sun; Wenjun Li; Xingbin Yang; Zhong Zhang (Journal of Food Engineering, 2025)

Effect of compound exposure to snowstorm and cold spell on acute myocardial infarction mortality - Jihong Hu; Zhiwei Li; Jingli Zhu; Qin He; Wenjun Cheng; Qianyao Cheng; Yinguang Fan; Hong Su; Huadong Wang; Zhongliang Bai; Xiuya Xing; Jian Cheng (Environmental Research, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Molecular insights into dissolved black carbons during adsorptive fractionation: Implications for photochemical reactivity and decontamination - Hanzhuo Luo; Zhigang Yi; Zixi Wang; Wenjun Wang; Yang Yang; Deyu Qin; Fanzhi Qin; Yin Zhou; Cheng Huang; Lei Chen; Guangming Zeng; Chen Zhang (Chemical Engineering Journal, 2025)

Effect of low temperature on myocardial infarction mortality in rural residents: comparison of daytime and nighttime exposure - Xiuya Xing; Wenjun Cheng; Qin He; Yiming Gai; Jingli Zhu; Qianyao Cheng; Yinguang Fan; Hong Su; Zhongliang Bai; Huadong Wang; Jian Cheng (International Journal of Biometeorology, 2025)

Mechanism of chlorobenzene removal in biotrickling filter enhanced by non-thermal plasma: Insights from biodiversity and functional gene perspectives - Miaomiao Qu; Yi Zheng; Zhuowei Cheng; Yun Shi; Wenjun Wang; Xiaoming Wu; Jianmeng Chen (Bioresource Technology, 2025)

Mechanism insights into metal-organic framework-derived carbon materials activating periodate for p-chlorophenol removal: The role of S and Fe co-doping - Wenjun Xiao; Ao Chen; Min Cheng; Weiping Xiong; Yang Liu; Jun Wang; Guangfu Wang; Gaoxia Zhang; Ling Li; Hongda Liu; Qingkai Shi (Water Research, 2025)

On-site visual quantification of alkaline phosphatase activity in cells using a smartphone-based approach - Caizhao Cheng; Wenjun Dong; Xingyu Zhao; Jiayun Chen; Sui Wang; Yufang Hu; Zhihe Qing (Analytica Chimica Acta, 2025)

Boosting H2O2 activation by Cu and Ce co-doped g-C3N4 for pollutants removal: From the free radical pathway to the non-free radical pathway - Qinghua Zou; Qingkai Shi; Min Cheng; Guangfu Wang; Wenjun Wang; Yongxi Chen; Ao Chen; Yuting Ma (Journal of Environmental Chemical Engineering, 2024)

Variations in volatile components and biological activities of essential oils from Citrus aurantium ‘changshanhuyou’ at different growth and ripening stages - Han Wang; Xinyue Zhou; Yong Deng; Ruyu Zhang; Kai Fu; Jiabao Huang; Qiong Huang; Cheng Zeng; Donghong Liu; Wenjun Wang (Food Research International, 2024)

Exceptional heatwaves and mortality in Europe: Greater impacts since the coronavirus disease 2019 outbreak - Zhiwei Li; Yinguang Fan; Zhiwei Xu; Hung Chak Ho; Shilu Tong; Cunrui Huang; Zhongliang Bai; Yiming Gai; Wenjun Cheng; Jihong Hu; Yufan Feng; Hao Zheng; et al. (Environmental Pollution, 2024)

Coaxial direct writing of ultra-strong supercapacitors with braided continuous carbon fiber based electrodes - Zhuoyuan Yang; Kehao Tang; Wenjun Song; Zefu Ren; Yuxuan Wu; Daewon Kim; Sirish Namilae; Yifei Yuan; Meng Cheng; Yizhou Jiang (Chemical Engineering Journal, 2024)

A full-field structural displacement reconstruction method for large-scale floating rafts in marine propulsion systems - Jianwei Cheng; Wenjun Bu; Wei Xu; Liang Shi; Xun Pan; Junqiang Fu; Shengwu Zhang (Ocean Engineering, 2024)

Extrusion-controlled lipid retention and distribution of wheat germ and its application combining exogenous starch - Ruihao Niu; Jingyi Wang; Jianwei Zhou; Huan Cheng; Jianle Chen; Wenjun Wang; Donghong Liu; Enbo Xu (Journal of Food Engineering, 2024)

Boosting peroxodisulfate activation by MIL-68(Fe) derived magnetic Fe3S4 nanosheets: Key role of sulfur vacancy - Feiyang Luo; Cheng Peng; Xinyu Chen; Wenjun Quan; Guohua Du; Jingjing Zhao; Xiaoxu Bo; Shaoyun Shan; Xinggen Yuan; Yanyan Deng; Tianding Hu (Journal of Environmental Chemical Engineering, 2024)

Corrigendum to “Effects of lacidophilin in a mouse model of low-grade colitis and nonalcoholic fatty liver disease” [Food Bioscience, 60 (2024), ISSN 2212-4292, FBIO_104469] - Yang Zhan; Xiaoying Cheng; Tao Li; Yingmeng Li; Denglong Sun; Fanghua Guo; Yong Sun; Qiong Li; Hua Zhang; Wenjun Liu (Food Bioscience, 2024)

Lactobacillus plantarum P9 ameliorates dysfunctional immune and metabolic homeostasis along the gut–liver axis in a nonalcoholic fatty liver disease with low-grade colitis mouse model - Yang Zhan; Qiong Li; Tao Li; Qinqin Yu; Yingmeng Li; Xiaoying Cheng; Yong Sun; Xiaoya Wang; Fanghua Guo; Hua Zhang; Wenjun Liu (Food Bioscience, 2024)

Engineering bioinspired rigid-soft architecture for enhanced stiffness and toughness in liquid-free stretchable ionic conductors - Hao Zhang; Wenjun Cheng; Mingyang Yang; Benyan Xu; Ximei Xu; Ming Zhou (Chemical Engineering Journal, 2024)

Distribution of modified Circumpolar Deep Water and its threat in Vincennes Bay, East Antarctica - Wenjun Ye; Lingqiao Cheng; Yujiro Kitade; Song Hu; Juncheng Zuo (Journal of Oceanology and Limnology, 2024)

Effects of lacidophilin in a mouse model of low-grade colitis and nonalcoholic fatty liver disease - Yang Zhan; Xiaoying Cheng; Tao Li; Yingmeng Li; Denglong Sun; Fanghua Guo; Yong Sun; Qiong Li; Hua Zhang; Wenjun Liu (Food Bioscience, 2024)

Crystallinity modulation and microenvironment engineering synergistically manipulate ROS generation on Ni single-atom photocatalysts - Yin Zhou; Fanzhi Qin; Wenjun Wang; Deyu Qin; Xiangmin Liu; Xiaoping Liu; Zhexian Wang; Cheng Huang; Hanzhuo Luo; Changlan Hou; Yunbo Zhai; Chen Zhang (Chemical Engineering Journal, 2024)

Prevalence and characterization of aminoglycoside resistance gene aph(2”)-If-carrying Campylobacter jejuni - Jin Kang; Cheng Zhang; Shuigen Wan; Wenjun Li; Wenbo Zhao; Longyu Li; Yanhong Shang; Xiang-Dang Du; Dejun Liu; Hong Yao (International Journal of Food Microbiology, 2024)

An up-to-date review: differential biosynthesis mechanisms and enrichment methods for health-promoting anthocyanins of citrus fruits during processing and storage - Jin Chen; Feifei Liu; Ricardo Antonio Wu; Jianle Chen; Wenjun Wang; Xingqian Ye; Donghong Liu; Huan Cheng (Critical Reviews in Food Science and Nutrition, 2024)

Overexpression of Nrf2 reverses ferroptosis induced by Arenobufagin in gastric cancer - Jiao Long; Wenjun Wang; Jing Chu; Yueyue Li; Meng Wang; Jingjing Su; Yuting Yang; GuoKai Wang; Qinglin Li; Hui Cheng (Toxicology and Applied Pharmacology, 2024)

Enhancement of antioxidant quality by Bacillus siamensis N-1 and the role of LcPOD4 in regulating peel browning and senescence of litchi fruit - Xin Wang; Shicheng Zou; Nanpu Cheng; Wenjun Jia; Wen Li; Yuanzhi Shao (Postharvest Biology and Technology, 2024)

NS5 hijacks TRAF3 to inhibit type I interferon signaling during duck Tembusu virus infection - Wenjun Cai; Yuhong Pan; Wanshuang Luo; Anchun Cheng; Mingshu Wang; Shun Chen; Juan Huang; Qiao Yang; Ying Wu; Di Sun; Sai Mao; Dekang Zhu; et al. (Veterinary Microbiology, 2023)

Effect of polystyrene microplastics on tetracycline photoconversion under simulated sunlight: Vital role of aged polystyrene - Zhexian Wang; Yunbo Zhai; Guangli Liu; Xiangmin Liu; Xiaoping Liu; Yin Zhou; Cheng Huang; Wenjun Wang; Min Xu (Science of The Total Environment, 2023)

Optimal sensor placement for leak location in water distribution networks based on EGAE clustering algorithm - Juan Li; Wenjun Zheng; Chunyue Wang; Menglong Cheng (Journal of Cleaner Production, 2023)

Integration of clinical characteristics and molecular signatures of the tumor microenvironment to predict the prognosis of neuroblastoma - Haiyan Cheng; Li Zhang; Shen Yang; Qinghua Ren; Saishuo Chang; Yaqiong Jin; Wenjun Mou; Hong Qin; Wei Yang; Xianwei Zhang; Wancun Zhang; Huanmin Wang (Journal of Molecular Medicine, 2023)

City-level environmental performance and the spatial structure of China's three coastal city clusters - Dan Wu; Yuying Lie; Li Liu; Ziye Cheng; Yujie Zhang; Yuxiang Yang; Wenjun Xiao; Suli Li; Guangyang Luo; Zhen Wang (Journal of Cleaner Production, 2023)

Electro-adsorption and reduction of Uranium(VI) by Fe3O4@COFs electrode with enhanced removal performance - Sen Yang; Zhouyi Ye; Xiaoya Cheng; Yuchun Wang; Zitong Luan; Wenjun Li; Baowei Hu (Chemical Engineering Journal, 2023)

LncRNA NEAT1 antagonizes the inhibition of melanoma proliferation, migration, invasion and EMT by Polyphyllin B - Wenjun Wang; Meng Wang; Xiaxia Liu; Xin Chen; Hui Cheng; Guokai Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

CO2 sequestration and CaCO3 recovery with steel slag by a novel two-step leaching and carbonation method - Can Cheng; Wenjun Huang; Haomiao Xu; Zhisong Liu; Xianwei Li; Hongzhi Shi; Yongmei Yu; Zan Qu; Naiqiang Yan (Science of The Total Environment, 2023)

The potential of different ripeness of blood oranges (Citrus sinensis L. Osbeck) for sale in advance after low-temperature storage: Anthocyanin enhancements, volatile compounds, and taste attributes - Jin Chen; Yanru Zhang; Feifei Liu; Jianle Chen; Wenjun Wang; Dan Wu; Xingqian Ye; Donghong Liu; Huan Cheng (Food Chemistry, 2023)

Experimental assessment the effects of saline discharge on plankton community of the recipient freshwater ecosystem – Inputs to scientific ballast water management of inland ports - Min Yang; Qiong Wang; Wenjun Wu; Xinyan Cheng; Huixian Wu (Limnologica, 2023)

Quantifying seasonal ground deformation in Taiyuan basin, China, by Sentinel-1 InSAR time series analysis - Wei Tang; Xiangjun Zhao; Gang Bi; Mingjie Chen; Siyu Cheng; Mingsheng Liao; Wenjun Yu (Journal of Hydrology, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Rapid Detection of Enterobacter cloacae With a Visualized Isothermal Recombinase Polymerase Amplification Assay - Juan Hu; Jing Xu; Yingzhi Lu; Lei Wang; Yan Wang; Cheng Chen; Wenjun Zhu (Current Microbiology, 2023)

Conversion of endogenous phenolic acid in brown rice by bioextrusion of mesophilic α-amylase - Yu Qin; Shuohan Ma; Jianwei Zhou; Dandan Li; Jianle Chen; Wenjun Wang; Huan Cheng; Zhengzong Wu; Jinhu Tian; Enbo Xu; Donghong Liu (Food Bioscience, 2023)

Insight into the effect of pyrolysis temperature on photoreactivity of biochar-derived dissolved organic matter: Impacts of aromaticity and carbonyl groups - Hanzhuo Luo; Eydhah Almatrafi; Wenjun Wang; Yang Yang; Danlian Huang; Weiping Xiong; Min Cheng; Chengyun Zhou; Yin Zhou; Qing Lin; Guoge Fang; Guangming Zeng; et al. (Science of The Total Environment, 2023)

Stronger selective constraints on the mitochondrial genome in flying fishes - Zufa Ding; Youwei Xu; Wenjun Chen; Yang Liu; Cheng Wang; Yuhan Niu; Kui Zhang; Ying Wang; Liandong Yang (Frontiers in Marine Science, 2023)
Flying fishes, which use their wing-like pectoral fins and hypocercal caudal fin to glide through the air to avoid underwater predators, have independently evolved flight behavior, making them ideal for the study of adaptive evolution. To investigate the adaptation of flight behavior in flying fishes and the origin of Beloniformes fishes, this study obtained the complete mitochondrial genomes of Cheilopogon nigricans and Oxyporhamphus micropterus and constructed the DNA sequences extracted from these newly sequenced mitochondrial genomes with the DNA sequences of 32 previously published mitochondrial genomes into a dataset for reconstructing the phylogenetic relationships of Beloniformes fishes. The phylogeny that emerged strongly supported the possibility that flying fishes developed from halfbeaks and the progressive transition of flying fishes from two-wing to four-wing gliding. The divergence time analysis showed that the split between the suborder Belonidei and the family Adrianichthyidae occurred roughly 77.08 Mya, which fell within the period of evolution of the Indian plate in the late Cretaceous. Selection analyses revealed that flying fishes have a lower dN/dS ratio than the other members of Beloniformes, indicating that flying fishes experienced stronger purifying selection to eliminate deleterious mutations to maintain efficient energy metabolism to adapt to flight behavior. Moreover, this work found the positively selected signal in the ND4 gene, suggesting that different mitogenomic genes might have undergone different selective patterns during adaptive evolution.

Comparative transcriptome analysis of non-germinated and germinated spores of Enterocytozoon hepatopenaei (EHP) in vitro - Yabin Dou; Leiting Zhang; Hui Shen; Sheng Zhang; Xiaohui Cao; Yi Qiao; Ge Jiang; Jie Cheng; Xihe Wan; Xianping Fan; Hui Li; Libao Wang; et al. (Journal of Invertebrate Pathology, 2023)

Novel-designed cobweb-like binder by “four-in-one” strategy for high performance SiO anode - Weihua Wang; Juan Ding; Zhenjie Liu; Yanbin Wei; Wenhua Cheng; Qingcui Liu; Weilu Zhang; XingChao Wang; Wenjun Zhang; Bao Wang; Jiulin Wang; Yudai Huang (Chemical Engineering Journal, 2023)

Insight into FeOOH-mediated advanced oxidation processes for the treatment of organic polluted wastewater - Hao Weng; Yang Yang; Chen Zhang; Min Cheng; Wenjun Wang; Biao Song; Hanzhuo Luo; Deyu Qin; Cheng Huang; Fanzhi Qin; Keteng Li (Chemical Engineering Journal, 2023)

Whole-genome sequencing and comparative genomic analysis of a pathogenic Enterocytozoon hepatopenaei strain isolated from Litopenaeus vannamei - Libao Wang; Hui Li; Wenjun Shi; Yi Qiao; Pan Wang; Zhijun Yu; Ran Zhao; Runhao Hu; Hui Shen; Jie Cheng; Ge Jiang; Xintong Huang; et al. (Aquaculture International, 2023)

Structure–performance correlation guided cerium-based metal–organic frameworks: Superior adsorbents for fluoride removal in water - Xiaofeng Tang; Wu Xia; Xiaolin Qu; Chaohai Wang; Wenjun Wang; Yuntao Liang; Yuxi Zeng; Weiping Xiong; Min Cheng; Biao Song; Chengyun Zhou; Xiaoying Zhao (Chemosphere, 2023)

Research on local buckling failure range of X80 buried steel pipeline under oblique-reverse fault - Chuan Ma; Xudong Cheng; Taozhi Xu; Lingyue Xu; Yun Wang; Kuo An; Wenjun Hu (Soil Dynamics and Earthquake Engineering, 2023)

Active chitosan/gum Arabic-based emulsion films reinforced with thyme oil encapsulating blood orange anthocyanins: Improving multi-functionality - Runan Zhao; Jin Chen; Songfeng Yu; Ruihao Niu; Zhehao Yang; Han Wang; Huan Cheng; Xingqian Ye; Donghong Liu; Wenjun Wang (Food Hydrocolloids, 2023)

Metal mixtures with longitudinal changes in lipid profiles: findings from the manganese-exposed workers healthy cohort - Xiaoting Ge; Guohong Ye; Junxiu He; Yu Bao; Yuan Zheng; Hong Cheng; Xiuming Feng; Wenjun Yang; Fei Wang; Yunfeng Zou; Xiaobo Yang (Environmental Science and Pollution Research, 2022)

Multi-Scale Object Detection Model for Autonomous Ship Navigation in Maritime Environment - Zeyuan Shao; Hongguang Lyu; Yong Yin; Tao Cheng; Xiaowei Gao; Wenjun Zhang; Qianfeng Jing; Yanjie Zhao; Lunping Zhang (Journal of Marine Science and Engineering, 2022)
Accurate detection of sea-surface objects is vital for the safe navigation of autonomous ships. With the continuous development of artificial intelligence, electro-optical (EO) sensors such as video cameras are used to supplement marine radar to improve the detection of objects that produce weak radar signals and small sizes. In this study, we propose an enhanced convolutional neural network (CNN) named VarifocalNet * that improves object detection in harsh maritime environments. Specifically, the feature representation and learning ability of the VarifocalNet model are improved by using a deformable convolution module, redesigning the loss function, introducing a soft non-maximum suppression algorithm, and incorporating multi-scale prediction methods. These strategies improve the accuracy and reliability of our CNN-based detection results under complex sea conditions, such as in turbulent waves, sea fog, and water reflection. Experimental results under different maritime conditions show that our method significantly outperforms similar methods (such as SSD, YOLOv3, RetinaNet, Faster R-CNN, Cascade R-CNN) in terms of the detection accuracy and robustness for small objects. The maritime obstacle detection results were obtained under harsh imaging conditions to demonstrate the performance of our network model.

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

Late Carboniferous back-arc rifting in Junggar Basin, NW China: implication for the rapid continental growth in accretionary orogens - Wenbin Tang; Xiaojun Wang; Xuguang Guo; Wenjun He; Yong Tang; Georgia Pe-Piper; David J. W. Piper; Zhaojie Guo; Feng Cheng; Wei Li; Yuanyuan Zhang (International Journal of Earth Sciences, 2022)

Buffer effect of MgO on Na2SO3 to stabilize S(IV) for the enhancement in simultaneous absorption of NOx and SO2 from non-ferrous smelting gas - Wenjun Huang; Sichao Li; Hongbin Wang; Peng Cui; Haomiao Xu; Can Cheng; Zan Qu; Naiqiang Yan (Environmental Science and Pollution Research, 2022)

Complete genome sequence and phylogenetic analysis of red seabream iridovirus isolated from a cage-cultured small yellow croaker (Larimichthys polyactis) in China - Gengshen Wang; Wei Xu; Haoxue Cheng; Jianjun Xie; Aixu Bai; Wenjun Xu; Qizhang Liang (Archives of Virology, 2022)

Causal Effect of Genetically Determined Blood Copper Concentrations on Multiple Diseases: A Mendelian Randomization and Phenome-Wide Association Study - Xiuming Feng; Wenjun Yang; Lulu Huang; Hong Cheng; Xiaoting Ge; Gaohui Zan; Yanli Tan; Lili Xiao; Chaoqun Liu; Xing Chen; Zengnan Mo; Longman Li; et al. (Phenomics, 2022)

Biomechanical Analysis of the External Fixation in a Lumbar Fracture Model: A Finite Element Study - Yijia Liao; Yiguo Yan; Yu Kang; Wenjun Wang; Xizheng Song; Wen Peng; Haibin Fu; Huarong Chen; Cheng Wang (Journal of Medical and Biological Engineering, 2022)
Purpose This study aimed to investigate the biomechanical characteristics of the external spinal fixation for treating lumbar fracture through finite element analysis (FEA) and provide a theoretical basis for its further application. Methods Two different models of L3 fracture fixed with the external spinal fixation and the internal fixation system respectively were constructed. The ROM, maximum stresses at L3, and the screws of the two models were measured under load control. Subsequently, the applied torque, the maximum stressed at L3, L1/2, L2/3, L3/4, L4/5 discs and the screws were analyzed under displacement control. Results Under load control, the external fixation model reserved more ROM than the internal fixation model (40.4–48.0% vs 30.5–41.0%). Compared to the internal fixation model, the maximum stresses at L3 and screws in the external fixation model were increased. Under displacement control, the external fixation model required fewer moments (N·mm) than the internal fixation model (flexion: 7500 vs 12,294; extension: 7500 vs 9027). Further, the maximum stresses at L3 and the screws in the external fixation model were greater than those of the internal fixation model, while the maximum stresses at the upper and lower adjacent discs of fixed segments were less than the internal fixation model. Conclusion Compared to the internal fixation system, the external fixation has a better stress distribution with the greater overall mobility. It theoretically reduces the stress concentration of the adjacent discs and the stress shielding of the fractured vertebral body.

Comprehensive Analysis of Aldehyde Dehydrogenases (ALDHs) and Its Significant Role in Hepatocellular Carcinoma - Senbang Yao; Wenjun Chen; He Zuo; Ziran Bi; Xiuqing Zhang; Lulian Pang; Yanyan Jing; Xiangxiang Yin; Huaidong Cheng (Biochemical Genetics, 2022)
Oxidative DNA damage is closely related to the occurrence and progression of cancer. Oxidative stress plays an important role in alcohol-induced hepatocellular carcinoma (HCC). Aldehyde dehydrogenase (ALDH) is a family of enzymes that plays an essential role in the reducing oxidative damage. However, how ALDHs family affects alcohol-related HCC remains obscure. We aimed to explore the correlation between the differential expression of ALDHs in patients with HCC and pathological features, as well as the relationship between ALDHs and prognosis, and finally analyze the possible mechanism of ALDHs in targeted therapy of HCC. The data of HCC were downloaded from The Cancer Genome Atlas (TCGA) database. This research explored the expression and prognostic values of ALDHs in HCC using Oncomine, UALCAN, Human Protein Atlas, cBioPortal, Kaplan–Meier plotter, GeneMANIA, Tumor Immune Estimation Resource, GEPIA databases, and WebGestalt. Low mRNA and protein expressions of ALDHs were found to be significantly associated with tumor grade and clinical cancer stages in HCC patients. In particular, the loss of ALDH expression is more obvious in Asians, and its effect on prognosis is far more significant than that in the White race. Our findings play an important role in the study of prognostic markers and anti-liver cancer therapeutic targets for the members of the ALDHs family, especially in patients with liver cancer in Asia.

Characteristics of the chemical composition and source apportionment of PM2.5 for a one-year period in Wuhan, China - Xiaoyu Zhang; Guixiang Ji; Xiaowu Peng; Lingya Kong; Xin Zhao; Rongrong Ying; Wenjun Yin; Tian Xu; Juan Cheng; Lin Wang (Journal of Atmospheric Chemistry, 2022)

Temperature-sensitive morbidity indicator: consequence from the increased ambulance dispatches associated with heat and cold exposure - Qingchuan Wang; Yiling He; Shakoor Hajat; Jian Cheng; Zhiwei Xu; Wenbiao Hu; Wenjun Ma; Cunrui Huang (International Journal of Biometeorology, 2021)

Extreme temperature indices in Eurasia in a CMIP6 multi‐model ensemble: Evaluation and projection - Yimin Zhao; Cheng Qian; Wenjun Zhang; Dong He; Yajie Qi (International Journal of Climatology, 2021)
It is important to project the changes in extreme temperature in Eurasia, where more than two‐thirds of the world's population reside. Employing Phase 6 of the Coupled Model Intercomparison Project (CMIP6) simulations and extreme temperature indices defined by the expert team on climate change detection and Indices, we firstly evaluate the performance of the CMIP6 models, and then project the spatial patterns of changes in extreme temperature in different periods under shared social‐economic Pathway scenarios and at different global warming levels. The results show that the performance of the CMIP6 models in simulating the indices of the coldest day (TXn), the coldest night (TNn), summer days (SU), tropical nights (TR) and frost days (FD) are good. Therefore, these five indices were selected for projection. Overall, TXn, TNn, SU and TR show an increasing trend and FD a decreasing trend, consistent with global warming in the future. The responses to global warming tend to be strongest in high latitudes for TXn and TNn, in high latitudes and high‐altitude areas for FD, and in some low‐latitude areas for SU and TR. At the local scale over Eurasia, where the change is larger than the regional median level, the changes in extreme temperature indices at 1.5°C of global warming above pre‐industrial levels are projected to be reduced by 30–55% and 55–85%, respectively, compared with the situation at 2.0°C and 3.0 warming. If global warming could be controlled to within 2.0°C, the changes in extreme temperature indices over Eurasia would be reduced by up to 60% compared with the situation at 3.0°C warming. Therefore, if global warming can be controlled to within a low warming target, the risk of extreme temperature change will be greatly reduced in these regions.

Transcriptome analysis reveals hub genes in the hepatopancreas of Exopalaemon carinicauda in response to hypoxia and reoxygenation - Wenjun Shi; Pan Wang; Runhao Hu; Xihe Wan; Hui Shen; Hui Li; Libao Wang; Yi Qiao; Ge Jiang; Jie Cheng; Zeyu Yang (Aquaculture International, 2021)

Molecular epidemiological characteristics of echovirus 6 in mainland China: extensive circulation of genotype F from 2007 to 2018 - Wenjun Cheng; Tianjiao Ji; Shuaifeng Zhou; Yong Shi; Lili Jiang; Yong Zhang; Dongmei Yan; Qian Yang; Yang Song; Ru Cai; Wenbo Xu (Archives of Virology, 2021)
Echovirus 6 (E6) is associated with various clinical diseases and is frequently detected in environmental sewage. Despite its high prevalence in humans and the environment, little is known about its molecular phylogeography in mainland China. In this study, 114 of 21,539 (0.53%) clinical specimens from hand, foot, and mouth disease (HFMD) cases collected between 2007 and 2018 were positive for E6. The complete VP1 sequences of 87 representative E6 strains, including 24 strains from this study, were used to investigate the evolutionary genetic characteristics and geographical spread of E6 strains. Phylogenetic analysis based on VP1 nucleotide sequence divergence showed that, globally, E6 strains can be grouped into six genotypes, designated A to F. Chinese E6 strains collected between 1988 and 2018 were found to belong to genotypes C, E, and F, with genotype F being predominant from 2007 to 2018. There was no significant difference in the geographical distribution of each genotype. The evolutionary rate of E6 was estimated to be 3.631 × 10 -3 substitutions site -1 year -1 (95% highest posterior density [HPD]: 3.2406 × 10 -3 -4.031 × 10 -3 substitutions site -1 year -1 ) by Bayesian MCMC analysis. The most recent common ancestor of the E6 genotypes was traced back to 1863, whereas their common ancestor in China was traced back to around 1962. A small genetic shift was detected in the Chinese E6 population size in 2009 according to Bayesian skyline analysis, which indicated that there might have been an epidemic around that year.

MST1 modulates Th17 activation in psoriasis via regulating TLR4-NF-κB pathway - Huayang Tang; Ze Guo; Xianfa Tang; Jinping Gao; Wenjun Wang; He Huang; Xiaodong Zheng; Hui Cheng; Yujun Sheng; Liangdan Sun (Human Cell, 2021)

A robust relationship between multidecadal global warming rate variations and the Atlantic Multidecadal Variability - Zhiyu Li; Wenjun Zhang; Fei-Fei Jin; Malte F. Stuecker; Cheng Sun; Aaron F. Z. Levine; Haiming Xu; Chao Liu (Climate Dynamics, 2020)

Observation and analysis of VOCs in nine prefecture-level cities of Sichuan Province, China - Wenjun Wang; Tingting Xiong; Wei Zhang; Bin Luo; Dongmei Wang; Xincheng Jiang; Zhihan Rao; Yan Jiang; Yue Liu; Huan Cheng; Xiaojing Luo; Meikun Fan; et al. (Environmental Monitoring and Assessment, 2020)

The contribution of bacteria to organic matter in coal-measure source rocks - Qingsong Cheng; Min Zhang; Guanghui Huang; Wenjun Zhang (Acta Geochimica, 2019)

Satellite observations of the aerosol direct radiative effect during a pollution episode in Nanjing, China, using high-resolution HJ-1 CCD imagery - Jian Chen; Jie Zhou; Wenjun Wang; Chen Cheng; Zhenbo Liu (International Journal of Remote Sensing, 2017)

LecRK-VII.1, a Lectin Receptor-Like Kinase, Mediates the Regulation of Salt Stress and Jasmonic Acid Response in Arabidopsis - Cheng Zhang; Jinyan Li; Xinhong Guo; Baode Zhu; Wenjun Xiao; Ping Wang; Miao Jiang; Shuai Hu; Xiutao Lu; Zhuang He; Ping Chen (Journal of Plant Growth Regulation, 2017)

CKB1 is involved in abscisic acid and gibberellic acid signaling to regulate stress responses in Arabidopsis thaliana - Congying Yuan; Jianping Ai; Hongping Chang; Wenjun Xiao; Lu Liu; Cheng Zhang; Zhuang He; Ji Huang; Jinyan Li; Xinhong Guo (Journal of Plant Research, 2017)

A glucuronokinase gene in Arabidopsis, AtGlcAK, is involved in drought tolerance by modulating sugar metabolism - Wenjun Xiao; Shuai Hu; Xiaoxun Zhou; Runyu Yao; Jingru Luo; Congying Yuan; Hongping Chang; Cheng Zhang; Ji Huang; Jinyan Li; Shucan Liu; Meiling Li; et al. (Plant Molecular Biology Reporter, 2017)

Biomarkers in Tubifex tubifex for the metalaxyl and metalaxyl-M toxicity assessment in artificial sediment - Shanshan Di; Ruiquan Liu; Cheng Cheng; Li Chen; Wenjun Zhang; Zhongnan Tian; Chunxiao Liu; Zhiqiang Zhou; Jinling Diao (Environmental Science and Pollution Research, 2017)

Relationship between molecular weight, monosaccharide composition and immunobiologic activity of Astragalus polysaccharides - Yiping Jiang; Xiaohui Qi; Kai Gao; Wenjun Liu; Na Li; Ningbo Cheng; Gang Ding; Wenzhe Huang; Zhenzhong Wang; Wei Xiao (Glycoconjugate Journal, 2016)

Influence of long-term irrigation with treated papermaking wastewater on soil ecosystem of a full-scale managed reed wetland - Aihui Chen; Huixing Liang; Tianming Chen; Wenjun Yang; Cheng Ding (Journal of Soils and Sediments, 2016)

Reduction of nitrobenzene with sulfides catalyzed by the black carbons from crop-residue ashes - Wenwen Gong; Xinhui Liu; Li Tao; Wei Xue; Wenjun Fu; Dengmiao Cheng (Environmental Science and Pollution Research, 2014)

A rice β-1,3-glucanase gene Osg1 is required for callose degradation in pollen development - Linglin Wan; Wenjun Zha; Xiaoyan Cheng; Chuan Liu; Lu Lv; Caixiang Liu; Zhanqi Wang; Bo Du; Rongzhi Chen; Lili Zhu; Guangcun He (Planta, 2011)

QSAR studies of imidazopyridine derivatives as Et-PKG inhibitors using the PSO-SVM approach - Zhengjun Cheng; Yuntao Zhang; Wenjun Zhang (Medicinal Chemistry Research, 2010)

Comparative study on rain splash erosion of representative soils in China - Qinjuan Cheng; Qiangguo Cai; Wenjun Ma (Chinese Geographical Science, 2008)